The Influence of Live Streaming, E-Wom, and Discounts on Impulsive Buying of Skincare Products at Tiktok Shop - Alifia Salsabila Putri; Claudya Marceline; Alawiahtul Aeni; Yono Maulana (Indonesian Journal of Business Analytics, 2024)
The development of TikTok Shop has created a trend for interactive and easy online shopping. This has an impact on increasing impulse buying behavior, especially for skincare products. This research aims to determine the influence of live streaming, E-WOM, and discounts on impulse purchasing behavior for skincare products at the TikTok Shop. This research uses a quantitative approach with a causal design. The sampling technique used non-probability and purposive sampling with a total of 126 TikTok Shop users. The data obtained was analyzed using SmartPLS. The results of this research show that live streaming, E-WOM, and discounts have a positive and significant influence on impulse purchases of skincare products at the TikTok Shop. Based on the findings of this research, sellers are advised to collaborate with influencers, develop a strong E-WOM strategy, and implement discount strategies to maximize sales